2014
DOI: 10.1007/s13277-014-2729-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of dual-specificity phosphatase 6 expression in non-small cell lung cancer

Abstract: Dual-specificity phosphatase 6 (DUSP6/MKP-3) is a mitogen-activated protein kinase phosphatase that regulates extracellular signal-regulated kinases (ERKs) activity via feedback mechanisms, with an increasingly recognized role in tumour biology. The aim of this study was to explore the role of DUSP6 expression in the prognosis of human non-small cell lung cancer (NSCLC). DUSP6 expression levels were evaluated by real-time quantitative reverse transcription polymerase chain reaction (PCR) in 60 NSCLC samples fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Consistent with our findings, studies of different types of solid tumors, including ovarian, breast, pancreatic, hepatocellular, esophageal, prostate, and lung carcinoma, reported that DUSP6 is underexpressed in highly proliferating tumor cells compared with normal cells [28,29,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] . This was thought to be due to DUSP6 acting as an ERK1/2specific negative regulator and suppression of the transcriptional activity of its downstream factors.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with our findings, studies of different types of solid tumors, including ovarian, breast, pancreatic, hepatocellular, esophageal, prostate, and lung carcinoma, reported that DUSP6 is underexpressed in highly proliferating tumor cells compared with normal cells [28,29,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] . This was thought to be due to DUSP6 acting as an ERK1/2specific negative regulator and suppression of the transcriptional activity of its downstream factors.…”
Section: Discussionsupporting
confidence: 89%
“…DUSP6-overexpressing SKOV3 cells also express lower levels of CyclinD3 (Figure 9). As DUSP6 is known to be a negative regulator of ERK1/2 [32][33][34][35][36][37] , we examined the levels of phosphor-ERK1/2 in these cells. Our study revealed that overexpression of DUSP6 decreased phospho-ERK1/2 levels in parallel with attenuated cyclin D3 expression (Figure 9b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cancer pathways, DUSPs generally play an antioncogenic role, by terminating the action of MAPKs, and the up ‐ regulation of DUSPs is considered to support the role of DUSP6 as a negative feedback regulator to restrain excess ERK signaling activation. Disruption of this feedback loop could therefore result in malignant transformation by providing cells with enhanced growth activity (Díaz‐García et al., 2015). Notably, however, DUSP6 knockdown by siRNA resulted in selective induction of apoptosis and impaired proliferation in A4‐15, but not in NIH/3T3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, hyperactivity of kinases in cancer is accompanied by down-regulation of phosphatases, which enzymatic action is directly opposite to that of kinases. The level of dual specificity phosphatase 6 (DUSP6) is reduced in lung cancer [85], and expression of dual-specificity phosphatase 2 (DUSP2) is low in breast, colon, lung, ovary, kidney, prostate, liver, and thyroid cancer [86]. It is important to note here that knockdown of both DUSP2 and DUSP6 significantly alters Golgi morphology [73].…”
Section: Ras Superfamily Gtpases Promote Golgi Fragmentation and Coormentioning
confidence: 99%